Extrabronchial symptoms and late phase reaction enhance the diagnostic value of aspirin bronchial challenge - Tworek, Damian; Zielińska-Wyderkiewicz, Ewa; Górski, Paweł; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Lysine aspirin (l-ASA) bronchial challenge can be used in the diagnostics of aspirin exacerbated respiratory disease. It is safer than oral challenge, however it is characterized by a lower sensitivity. Aim: We sought to investigate whether additional indicators of the positive result of l-ASA bronchial challenge, i.e. late phase reaction (LPR) and extrabronchial symptoms (EBS), may enhance its diagnostic value. Material and methods : Sixty-seven patients with a positive history of asthma exacerbated by aspirin and/or other non-steroidal inflammatory drugs underwent l-ASA bronchial challenge. The control groups comprised 15 aspirin tolerant asthmatics and 15 healthy subjects. Forced expiratory volume in 1 s (FEV1) and 24-hour peak expiratory flow (PEF) measurements were performed in all subjects in order to recognize early and late response to l-ASA. All subjects underwent oral ASA challenge 2 weeks after l-ASA bronchial challenge. Results : Basing on FEV1 and PEF results, early reaction was present in 50.7% of patients, early and LPR in 29.9% and LPR in only 10.4% of aspirin exacerbated respiratory disease patients. The EBS were noted in 31.3% of subjects. Inclusion of LPR and EBS as positive criteria of the challenge increased sensitivity to 94.0%. Conclusions : These results indicate that both LPR and EBS should be considered as positive criteria of aspirin bronchial challenge as they enhance its diagnostic value.